PENGELOLAAN WAKAF PRODUKTIF UNTUK MENINGKATKAN KESEJAHTERAAN UMAT: Studi di Dusun Tamanayu Desa Jatirejoyoso Kecamatan Kepanjen Kabupaten Malang - Eka Chanani Bahri (LP3M IAI Al-Qolam, 2022)
The land endowment which was later built as an educational center in Tamanayu Jatirejoyoso, Kepanjen Malang, became the focus of this research as one of the efforts to improve the welfare of the people. If the waqf is optimally managed, it will become truly productive waqf in producing productive human resources as well. This is a descriptive qualitative research in which the data collection uses observation, interview, and documentation methods. The results showed that the waqf land management carried out in Tamanayu, especially TK Nurul Hidayah, was quite good. The benefits that are used as goals are in the form of improving the quality of human resources. Utilization in this field is considered appropriate and very helpful when viewed from the needs of the local community. However, when viewed from the number and extent of waqf land in Tamanayu, the use of waqf land is still not optimal. There are 13 waqfs in 2021 but only one piece of land with an area of ​​600 m2 is managed productively. Nurul Hidayah Kindergarten can be used as a reference for waqf land management, the benefits of which can continue in forms of development that provide more benefits.